Hubungan Motivasi terhadap Keberhasilan Pengobatan Endometriosis - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Romaito Nasution; Milna Sari (Pusat Riset dan Inovasi Nasional, 2024)
This meta-analysis investigates the relationship between patient motivation and the success of endometriosis treatment, encompassing 25 studies with a total of 3,782 patients. A strong positive correlation was found (r = 0.68, p < 0.001) between motivation levels and treatment outcomes for endometriosis. Additional findings include: First, patients with high motivation exhibited a significantly greater reduction in pain (SMD = 1.24, 95% CI [0.98, 1.50]) and a more substantial improvement in quality of life (SMD = 0.89, 95% CI [0.67, 1.11]); Second, analysis of factors influencing motivation revealed scores related to understanding of the disease (β = 0.41, p < 0.001), social support (β = 0.38, p < 0.001), and the quality of the doctor-patient relationship (β = 0.45, p < 0.001); Third, motivational interventions were demonstrated to be effective in enhancing treatment outcomes for endometriosis (SMD = 0.94, 95% CI [0.73, 1.15], p < 0.001). Lastly, intrinsic motivation showed a stronger correlation with treatment outcomes for endometriosis (r = 0.73, 95% CI [0.65, 0.79]) compared to extrinsic motivation (r = 0.54, 95% CI [0.45, 0.62]). These findings extend the results of Facchin et al. (2017) regarding the role of psychological factors in the quality of life of endometriosis patients and support Deci and Ryan's (2000) theory on the importance of intrinsic motivation. Furthermore, in contrast to previous studies focusing on biomedical aspects, this research reveals the crucial role of psychological factors in the management of endometriosis treatment, underscoring the significance of Engel's (1977) proposed biopsychosocial approach. Consequently, these results provide a strong empirical foundation for integrating motivational enhancement strategies into standard care protocols for endometriosis and paving the way for a more holistic and effective approach to managing this condition.